Reading young adult South Africans’ reading of national television news - Musa Ndlovu (Communicare)
This article introduces a theoretical perspective on young adults’ television news-viewing choices grounded in the synthesis of reception aesthetics, socialisation theory and qualitative research methodology. It argues that this theoretical framework allows for a deeper contextual reading of the reader-text relationship and for the argument that, despite post-apartheid social transformation, young adult South Africans’ readings of locally produced television news texts are still ideologically situated sociocultural imports traceable to their differential class, race and gender positions in the country’s social structure. Evidence produced through focus-group interviews is used to support the position of the introduced theoretical framework.